2022
DOI: 10.1186/s12958-022-00938-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotinamide on follicular development and the quality of oocytes

Abstract: Background Nicotinamide (NAM) is an important antioxidant, which is closely related to female fertility, but its role has not been clearly elucidated. The purpose of the present study was to investigate the effects of NAM on follicular development at different stages and the quality of oocytes. Methods The concentration of NAM in follicular fluid (FF) of 236 women undergoing in vitro fertilization (IVF) was ascertained by enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…Therefore, how to improve the oocyte quality of infertile women with diabetes to achieve comparative developmental competence with healthy females is an important research and clinical topic. The IVM culture medium plays critical role in achieving higher IVM rate of oocytes [ 14 , 34 ]. Several drugs have been proved to have the ability to improve oocyte quality when supplemented in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, how to improve the oocyte quality of infertile women with diabetes to achieve comparative developmental competence with healthy females is an important research and clinical topic. The IVM culture medium plays critical role in achieving higher IVM rate of oocytes [ 14 , 34 ]. Several drugs have been proved to have the ability to improve oocyte quality when supplemented in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, overcoming the problems correlated with IVM by optimizing the IVM system is of significant importance. Previous studies have shown that supplementation of antioxidants during the IVM process could improve the oocyte quality and reduce the damage caused by oxidative stress [ 5 , 14 , 15 ]. In line with this finding, we aimed to explore novel strategies to improve the maturation rate and quality of IVM oocytes of patients suffering from diabetes, thereby increase the assisted reproductive efficiency and ultimately improve the reproductive outcomes of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…TW-7 (25, 50, and 100 μmol/L), oxamate (5 mmol/L, a glycolysis inhibitor that reduces intracellular lactate levels [ 47 , 48 ], HY-W0130032A, MedChemExpress, Monmouth Junction, NJ, USA), and lactate (5 mmol/L, a histone lactation agonist [ 28 ], HY-B2227B, MedChemExpress) were supplemented in the warming, recovery, PA and IVC medium. Hydrogen peroxide (H 2 O 2 , 100 μmol/L) was added to the IVC medium as an oxidative stress inducer for 1 h [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maintenance of follicular NAD + levels can be achieved by supplementation with NAD + precursors. Supplementation with NAD + precursors (such as NMN, NR, NA, and NAM) protects the first meiosis of aged oocytes and reduces the incidence of defects in spindle components such as spindle and chromosome and aneuploidy while improving the number of pregnancies and live births in aged mouse ( Table 1 ) [ 32 , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ]. Most of the mechanisms that NAD + precursors protecting ovarian preservation are through improving mitochondrial function, decreasing ROS levels, reducing oxidative damage, inhibiting DNA damage, and apoptosis ( Fig.…”
Section: Effects Of Nad + and Its Precursors On Re...mentioning
confidence: 99%